The Effect Of Product Quality And Price On Customer Satisfaction At Teras Kopi Clinix Bagan Sinembah - Muhammad Arvio Lesmana L. Toruan; Aulia Indra; M. Irwansyah Hasibuan (Citakonsultindo, 2026)
The development of the coffee business in Bagan Sinembah has experienced rapid growth in the last five years, from only a handful of shops such as Teras Kopi Clinix to hundreds of national outlets (Kopi dari Hati, JCO Coffee, Tomoro Coffee, Point Coffee) and local MSMEs (Dongan Coffee, Still Coffee, Teduh Coffee, etc.), as well as mobile coffee businesses (Ido Coffee, Roda Kopi, Gayo Espresso, etc.). This tight competition demands a superior strategy, where product quality and price are the main determinants of customer satisfaction, as stated by Eltantian et al. (2023) that satisfaction arises from expectations of product or service performance, and Maharani et al. (2025) who emphasize the role of service and price balance in consumer loyalty. This study analyzes the influence of product quality and price on customer satisfaction at Teras Kopi Clinix Bagan Sinembah, with the aim of identifying consumer preference factors, key factors for business sustainability, and business strategies for maintaining raw material quality and competitiveness. Through an in-depth analytical approach, the results are expected to provide recommendations for local coffee shop managers on maintaining customer loyalty amidst increasingly fierce competition.